Dynamics of Liénard Optoelectronic Oscillators - Romeira, B.; Figueiredo, J.; Ironside, Charlie; Javaloyes, J. (Springer, 2013)
In this chapter we present a comprehensive study on the dynamics of novel nonlinear optoelectronic oscillators (OEO) modeled by Liénard OEO systems. The OEO dynamical systems are based on negative differential resistance resonant tunneling diode oscillators incorporating a photoconductive region and laser diodes. The modeling results are in a good agreement with the wide variety dynamics that has been observed in recent experimental work spanning from self-sustained relaxation oscillations to injection locking and chaotic behaviors in both electrical and optical domains. Potential applications range from generation of periodic and chaotic signals for chaos-based communication schemes to highly stabilized OEOs for microwave-photonic systems.